Immersive Virtual Mine - Soares, L. P.; Pires, F.; Varela, R.; Bastos, R.; Dias, J.; Carvalho, N. (In Proceedings ofProceedings of SIACG 2009 IV Iberoamerican Symposium in Computer Graphics, 2009)
A mine visit simulation has special features that lead to complex problems like tunnels behavior. The use of immersive virtual reality environments produces high quality simulation since it is possible to control several feedback mechanisms like the degree of luminance of produced imagery and spatial sound. Projection infrastructure and tracking were specified to produce the best results for this kind of simulation. In order to achieve the simulation, distributed algorithms were developed to run in a cluster solution that drives a 4 sided CAVE like environment. Authoring techniques were also developed to enable fast production of new content for the simulation.